INVESTIGATE THE CRITICAL FACTORS OF BECOMING A SUCCESSFUL PRODUCT MANAGER - Cheng-Han Hsieh; Yu-Jen Cheng (PEOPLE: International Journal of Social Sciences, 2025)
Successful launching and marketing new products are primely related to the product manager. Therefore, understanding what defines a qualified product manager is crucial for the success of the company. This paper adopts the DANP methodology introduced by Ou Yang et al. (2008), which integrates DEMATEL and ANP, to investigate the criteria and their priority for a successful product manager. We firstly develop four clusters and review the literature of each cluster to extract its related criteria, resulting in fifteen criteria in total; then consult with 10 scholars/experts; finally, interview face-to-face with 10 senior managers to collect their practical opinions. The expected results include: (1) Identify the critical criteria for becoming a successful product manager; (2) Understand the causal relationships among the sets of clusters of successful product manager; (3) Construct the impact-relationship map (IRM) for successful product manager; (4) Rank the importance of each criterion to indicate their priority in a successful product manager; (5) Provide evaluation criteria for companies when they are searching for product managers; and (6) Provide a reference for those who are aspiring to become product managers.